2016
DOI: 10.1016/j.actamat.2016.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local stress fields on twin characteristics in HCP metals

Abstract: a b s t r a c tWe study the effect of nearest neighboring grains on the propensity for {1012} twin growth in Mg and Zr. Twin lamellae lying within one grain flanked by two neighboring grains with several orientations are considered. The fields of resolved shear stress on the twin system are calculated in the multicrystal using a three-dimensional full-field crystal plasticity Fast Fourier Transform approach. The calculations were carried out for Mg and Zr using slip threshold stresses corresponding to 300 K an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(31 citation statements)
references
References 70 publications
(36 reference statements)
0
28
0
Order By: Relevance
“…In addition, it was experimentally noticed that some twinning modes in magnesium have "abnormal", i.e., "non-Schmid" behavior [18]. The reason was attributed to the fact that the local stresses differ from the global ones [19], but to our knowledge, there are no convincing quantitative experimental results that can confirm this explanation. Non-Schmid behavior was also observed at least for slip deformation in bcc metals.…”
Section: Shears Used In the Theories Of Deformation Twinningmentioning
confidence: 96%
“…In addition, it was experimentally noticed that some twinning modes in magnesium have "abnormal", i.e., "non-Schmid" behavior [18]. The reason was attributed to the fact that the local stresses differ from the global ones [19], but to our knowledge, there are no convincing quantitative experimental results that can confirm this explanation. Non-Schmid behavior was also observed at least for slip deformation in bcc metals.…”
Section: Shears Used In the Theories Of Deformation Twinningmentioning
confidence: 96%
“…Past research concentrated mostly in characterizing these processes with transmission electron microscopy (TEM) on post-deformation specimens 2124 . Most recently, in situ experiments 7,2529 , full-field crystal plasticity modeling 3035 and atomistic simulations 5,36,39 have expanded the understanding of twin formation and its effect on material behavior. There is an interrelation between twin domain, twin interface, crystallographic defects and local stress fields that conditions twin propagation and hardening.…”
Section: Introductionmentioning
confidence: 99%
“…There is an interrelation between twin domain, twin interface, crystallographic defects and local stress fields that conditions twin propagation and hardening. A twin transformation (~13% shear for {} tensile twin in Mg) induces local stress fields in the vicinity of twins 3540 . The magnitude of these local stresses is determined, in part, by the ability of neighboring grains to accommodate the transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While recent experimental measurements and modeling studies have revealed large localized stress fields near the tips of twins 10 12 , it is generally believed that twin transformation strain is one of the key factors that can relax grains resolved stresses in HCP alloys 13 . For instance, with the use of neutron diffraction it was shown that formation of twins results in stress relaxation in the texture component selected by the diffraction of an incident beam 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%